(untitled) (Research, Society and Development, 2022)
In the current scenario of Medicine, in which evidence-based studies have gained more and more space in the field of research, the chosen disease screening methods will be those that can be proven to bring more accurate diagnoses to patients. Within the aspect of Oncological Medicine, its lines of treatment and prognoses must have a sensitized and specific research, in order to avoid complications greater than the disorder itself. Such failures can be harmful to the patient, at different levels of health aspects. Thus, in this study, an individualized cardiological assessment was carried out through the ECG (electrocardiogram) in order to clarify the main cardiological changes caused by cancer treatment at the Hospital de Câncer de Cascavel - UOPECCAN in children and adolescents. are the main changes and their possible correlations among them that can lead to some harm to the patient undergoing cancer treatment.